2020
DOI: 10.15244/pjoes/119477
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Organic Mulch on Soil Moisture and Nutrients in Karst Area of Southwest China

Abstract: Based on the typical engineering water shortage and soil degradation of sloping farmland in the karst area of southwest China, this experiment is to explore the suitable organic mulch materials and application rate and to provide theoretical reference for the regional soil moisture conservation and fertility enhancement. The maize monoculture was set as control (CK), five straw mulch treatments (20%, 40%, 60%, 80%, 100%, SM1-SM5) and four biochar mulch treatments (25%, 50%, 75%, 100%, BM1-BM4), which were set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Different soil microbes have distinct functions and hereditary characters to affect soil nutrients availability and elements cycling (Cairns, Robertson, Sigmund, & Street‐Perrott, 2020; Saletnik et al, 2017; Xing et al, 2019). The carbon‐rich nature of biochar also suggests potential impacts on carbon mineralization that is driven by diverse soil microbial communities (Chen et al, 2018; Hardy, Sleutel, Dufey, & Cornelis, 2019; Li, Li, et al, 2020; Li, Wang, Chang, Jiang, & Song, 2020). However, while the positive effects of biochar on plants are widely documented (Bai et al, 2022; Kochanek et al, 2022; Mansoor et al, 2021), there is little information on the consequences of field application of biochar on woody crop (Sichuan pepper) stands and microbial communities in anti‐dip karstic soils (Gan, He, Qin, & Li, 2020b; Li, Li, et al, 2020; Li, Wang, et al, 2020; Zhou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different soil microbes have distinct functions and hereditary characters to affect soil nutrients availability and elements cycling (Cairns, Robertson, Sigmund, & Street‐Perrott, 2020; Saletnik et al, 2017; Xing et al, 2019). The carbon‐rich nature of biochar also suggests potential impacts on carbon mineralization that is driven by diverse soil microbial communities (Chen et al, 2018; Hardy, Sleutel, Dufey, & Cornelis, 2019; Li, Li, et al, 2020; Li, Wang, Chang, Jiang, & Song, 2020). However, while the positive effects of biochar on plants are widely documented (Bai et al, 2022; Kochanek et al, 2022; Mansoor et al, 2021), there is little information on the consequences of field application of biochar on woody crop (Sichuan pepper) stands and microbial communities in anti‐dip karstic soils (Gan, He, Qin, & Li, 2020b; Li, Li, et al, 2020; Li, Wang, et al, 2020; Zhou et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The carbon‐rich nature of biochar also suggests potential impacts on carbon mineralization that is driven by diverse soil microbial communities (Chen et al, 2018; Hardy, Sleutel, Dufey, & Cornelis, 2019; Li, Li, et al, 2020; Li, Wang, Chang, Jiang, & Song, 2020). However, while the positive effects of biochar on plants are widely documented (Bai et al, 2022; Kochanek et al, 2022; Mansoor et al, 2021), there is little information on the consequences of field application of biochar on woody crop (Sichuan pepper) stands and microbial communities in anti‐dip karstic soils (Gan, He, Qin, & Li, 2020b; Li, Li, et al, 2020; Li, Wang, et al, 2020; Zhou et al, 2019). Moreover, many studies focus on the effects of biochar on plants, soils, or microorganisms individually; however, the effect of biochar on the nexus among plants, soil, and microorganisms remains underexplored and poorly understood (Chen, Ma, et al, 2018; Kolton, Graber, Tsehansky, Elad, & Cytrya, 2017; Nash et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the beneficial role of mulching for enhancing activity of soil biota, helping in soil rehabilitation, and improving the nutrient availability in the soil (Jabran 2019), water conservation is another advantage of soil mulching. Li et al (2020) reported that straw mulch played an important role in water conservation and fertility enhancement. Thus, our findings proved the beneficial effect of mulching for enhancing the nutrient status of calcareous soil under moderate water supply (I80) because of raising available K (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Karst rocky desertification leads to significant negative impacts to the local environment and socio-economic conditions (Chen et al, 2011;Jiang et al, 2014). At present, ecological restoration measures such as afforestation and soil improvement have been applied to combat karst rocky desertification (Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%